2018
DOI: 10.1038/s41380-018-0298-8
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic data and cognitively defined late-onset Alzheimer’s disease subgroups

Abstract: Categorizing people with late-onset Alzheimer’s disease into biologically coherent subgroups is important for personalized medicine. We evaluated data from five studies (total n = 4050, of whom 2431 had genome-wide single-nucleotide polymorphism (SNP) data). We assigned people to cognitively defined subgroups on the basis of relative performance in memory, executive functioning, visuospatial functioning, and language at the time of Alzheimer’s disease diagnosis. We compared genotype frequencies for each subgro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 28 publications
6
95
0
Order By: Relevance
“…Previous studies regarding Alzheimer's disease, neuroticism, or asthma found that items or symptoms showed, to some degree, increased ORs between the case loci and control loci compared to those from previous studies using broadly defined disease diagnoses (9)(10)(11). These findings may indicate that GWAS based on a symptom or an item could identify genetically more homogeneous subgroups and let us hypothesize that a relatively reasonable combination of symptoms or items could identify more genetically homogeneous subgroups.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Previous studies regarding Alzheimer's disease, neuroticism, or asthma found that items or symptoms showed, to some degree, increased ORs between the case loci and control loci compared to those from previous studies using broadly defined disease diagnoses (9)(10)(11). These findings may indicate that GWAS based on a symptom or an item could identify genetically more homogeneous subgroups and let us hypothesize that a relatively reasonable combination of symptoms or items could identify more genetically homogeneous subgroups.…”
Section: Discussionmentioning
confidence: 69%
“…First, Chaste and colleagues used one item or symptom alone, whereas we used combinations of them with a machine learning method. DeMichele-Sweet and colleagues reported that subgrouping only by having psychosis could lead to the identification of limited loci that had small effects (59), but Mukherjee and colleagues found a substantial number of suggestive loci that had extreme ORs after categorizing persons with Alzheimer's disease based on relative performance across cognitive domains by modern psychometric approaches (9). It may be necessary to utilize an appropriate combination of data to reveal masked patterns of data sets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we tested the associations between the 48 PRSs for AD-associated traits and five AD subgroups defined in the Executive Prominent Alzheimer’s Disease (EPAD) study of cognitively-defined AD subgroups, i.e. isolated relative impairments in memory, language, and visuospatial functioning, no domain with an isolated relative impairment, and multiple domains with relative impairments ( Methods ) [21, 22]. The PRS for maternal family history of AD and dementia was strongly and consistently associated with all five cognitively defined AD subgroups ( Supplementary Table 8 ), with the group with isolated relative memory impairment showing the strongest association (p=3.3e-16), which is consistent with the higher frequency of APOE ε 4 in this subgroup [21].…”
Section: Resultsmentioning
confidence: 99%
“…We also assessed the rate of decline in memory, executive function, visuospatial function, and language across the subtypes. Definitions, collection, and standardization of these decline measures can be found in previously published work 24 .…”
Section: Methodsmentioning
confidence: 99%